Training for Teachers and Students of MTs Rodlotul Khuffadz Sorong in Using the Book Al-Miftah Lil Ulum for Nahwu and Sharaf Learning - Al Jawad, Ulil Albab; Abdillah M., Fardan; Hidayat, Fadli; Mahmud, Azkiya; Harto, Sumber (Bhinneka Publishing, 2025)
This community service program aimed to enhance the competencies of teachers and students at MTs Rodlotul Khuffadz Sorong in using the classical book Al-Miftah Lil Ulum for Nahwu and Sharaf learning. The training adopted a participatory and practical approach, including theoretical sessions, guided practice, and group discussions. The program was implemented over three days and followed by evaluation through pre-test and post-test instruments. Results showed a significant improvement in participants' understanding, with average scores rising from 45% to 78%. In addition to cognitive gains, the training also shifted participants' attitudes toward Arabic grammar, transforming perceptions of Nahwu and Sharaf from difficult and monotonous subjects into engaging and meaningful learning experiences. The use of talaqqi and musyafahah methods, along with structured group activities, proved effective in fostering active learning and collaborative understanding. Despite challenges such as limited time and varied participant backgrounds, the training demonstrated that classical text-based learning can be successfully implemented in formal madrasah settings. The outcomes suggest strong potential for integrating Al-Miftah Lil Ulum into the Arabic language curriculum and call for continued training and support at institutional and policy levels.